The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.31235/osf.io/u7qfr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lithic morphological organisation: Gahagan bifaces from the Southern Caddo Area

Abstract: This analysis of Gahagan biface morphology enlists the three largest samples of Gahagan bifaces, to include that of the type site (Gahagan Mound) as well as the Mounds Plantation and George C. Davis sites. Results indicate a significant difference in Gahagan biface morphology at the Mounds Plantation site when compared with Gahagan bifaces from the Gahagan Mound and George C. Davis sites. Tests for allometry and asymmetry were not significant. The test of morphological disparity indicates that Gahagan bifaces … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Superficially, this constellation of landmarks and semilandmarks appears similar to the 2D configuration used in the previous study (Selden Jr. et al, 2018). However, this landmarking protocol captures the morphological variation that articulates with axial twisting introduced by knappers through the practise of bifacial beveling (Figure 9) (Selden Jr., 2020).…”
Section: Final Configuration 445supporting
confidence: 79%
See 4 more Smart Citations
“…Superficially, this constellation of landmarks and semilandmarks appears similar to the 2D configuration used in the previous study (Selden Jr. et al, 2018). However, this landmarking protocol captures the morphological variation that articulates with axial twisting introduced by knappers through the practise of bifacial beveling (Figure 9) (Selden Jr., 2020).…”
Section: Final Configuration 445supporting
confidence: 79%
“…This contribution follows a recent study of Gahagan biface morphology that enlisted the three largest samples in the southern Caddo area from the Gahagan Mound (16RR1), George C. Davis (41CE19), and Mounds Plantation (16CD12) sites ( Figure 1) (Selden Jr. et al, 2018). The results of that study indicated a significant difference in shape between Gahagan bifaces found at the Mounds Plantation site compared with those found at the Gahagan Mound and George C. Davis sites (Selden Jr. et al, 2018, Figure 7).…”
mentioning
confidence: 61%
See 3 more Smart Citations